Effect of working fluids in a novel geothermal-based integration of organic-flash and power/cooling generation cycles with hydrogen and freshwater production units. (13th August 2021) - Cao, Yan; Dhahad, Hayder A.; Togun, Hussein; Hussen, Hasanen M.; Anqi, Ali E.; Farouk, Naeim; Issakhov, Alibek; Parikhani, Towhid
Abstract: One of the essential steps to design energy conversion-based systems is choosing an efficient working fluid under the design goals to access stable products with high efficiency and overcome environmental issues. In this regard, the current paper is motivated to devise and evaluate a novel geothermal-driven multigeneration system under the effect of various working fluids. The proposed system consists of a flash-binary geothermal power plant, an organic flash cycle (OFC), a power/cooling subsystem (an organic Rankine cycle (ORC) and a thermoelectric generator incorporated with a compression refrigeration cycle), and freshwater and hydrogen production units utilizing a humidification-dehumidification desalination unit and a low-temperature electrolyzer. Considering the design potential of the OFC and ORC, four different environmentally-friendly working fluids, i.e., R123 and R600 in the OFC and R1234yf and R1234ze(e) in the ORC are selected and classified in four groups to introduce the best one, under the energy, exergy, and economic (3E analysis) approaches. Also, the whole system is optimized through a genetic algorithm, respecting the optimal solution for the energy efficiency and unit exergy cost of the products. According to the results, R123/R1234ze(e) shows the highest cooling, hydrogen, freshwater production rates, and energy efficiency. Likewise, the maximum power generation and exergy efficiency belong to R600/R1234ze(e). Moreover, R600/R1234yf has the lowest unit exergy cost of products. Highlights: Design of a new geothermal system to produce power, cooling, hydrogen, and freshwater. Integration on organic flash and organic Rankine cycles for multi-heat recovery. Classifications of four different environmentally-friendly organic working fluids. Comparison of thermodynamic and economic performances of selected classifications. R123/R1234ze(e) acts its best among selected classifications.